2017
DOI: 10.1155/2017/8984516
|View full text |Cite
|
Sign up to set email alerts
|

Closer to a Uniform Language in Colposcopy: Study on the Potential Application of 2011 International Federation for Cervical Pathology and Colposcopy Terminology in Clinical Practice

Abstract: As the newest colposcopic terminology, the 2011 International Federation for Cervical Pathology and Colposcopy (IFCPC) classification provides standardized interpretation of colposcopic findings. In this study, we analyzed the colposcopic accuracy and the significance of individual findings according to the 2011 IFCPC classification in 525 patients, reviewed by 13 trained colposcopists. Results show that colposcopic diagnoses are in 64.95% perfect agreement with cervical pathology, with 63.64% sensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 23 publications
3
13
2
Order By: Relevance
“…9,13,14,16 Therefore, as the IFCPC nomenclature for the vagina becomes better understood and applied-providing standardized interpretations of and an organized, comprehensive classification system for colposcopic findings of vaginal lesions-the accuracy of the colposcopic diagnosis on VaIN is being improved and approaching that for the cervix. [19][20][21][22] However, it should be noted that, in our study, the agreement rate was the lowest (35.71%) in the HSIL group, which was significantly different from that of the other lesion grade groups (LSIL and carcinoma). Although the accuracy of colposcopy for detecting VaIN was improved due to the implementation of the IFCPC nomenclature, more definite and practical findings for highgrade VaIN colposcopic patterns may be needed in further studies.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…9,13,14,16 Therefore, as the IFCPC nomenclature for the vagina becomes better understood and applied-providing standardized interpretations of and an organized, comprehensive classification system for colposcopic findings of vaginal lesions-the accuracy of the colposcopic diagnosis on VaIN is being improved and approaching that for the cervix. [19][20][21][22] However, it should be noted that, in our study, the agreement rate was the lowest (35.71%) in the HSIL group, which was significantly different from that of the other lesion grade groups (LSIL and carcinoma). Although the accuracy of colposcopy for detecting VaIN was improved due to the implementation of the IFCPC nomenclature, more definite and practical findings for highgrade VaIN colposcopic patterns may be needed in further studies.…”
Section: Discussioncontrasting
confidence: 85%
“…This was similar to Stuebs’ report 16 but different from previous studies on the cervix, which showed that the IFCPC classification was relatively balanced in overestimated and underestimated diagnoses in the cervix. 16 , 19 Moreover, the negative predictive values were much higher than the positive predictive values for both high-grade and low-grade VaIN. This supported the idea that colposcopic patterns are more likely to be overestimated than underestimated by observers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results showed the agreement between histopathology and colposcopy was 65.07% with weighted kappa = 0.5966. It was equal to Li et al's of 64.95% with consistency of kappa = 0.436, Fan et al's of 65.5% with weighted kappa strength 0.494 and Prabhakaran's of 65.7% [28][29][30]. Although IFCPC nomenclature was only moderate, it was better than Swede Score, RCI, modi ed RCI and IFCPC nomenclature [7,8,[31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 72%
“…primarily never screened recently). Studies comparing the Reid Colposcopic Index (RCI), the Swede score, and the International Federation for Cervical Pathology and Colposcopy (IFCPC) classification have shown slightly different performances 18,19. Most studies do not report the method of colposcopy used, often simply stating that "acetowhiteness and vascular change" was assessed and making a colposcopic impression of disease.…”
mentioning
confidence: 99%